Naturalism, Normativity, and the Study of Religion - Mundra, Anil (Religions, 2017)
This article repudiates the common view that the study of religion, in order to qualify as academic, must be descriptively neutral and naturalistic rather than normative or prescriptive. Following philosophers like John McDowell, John Cottingham, and Tyler Roberts, I claim that such a methodological stance amounts to viewing humans as determined rather than free agents. On the basis of W.V.O. Quine and Donald Davidson's analysis of translation, I argue that normativity is ineliminable from humanistic scholarship, which is itself inextricable from religious studies. Robert Pippin and Thomas A. Lewis's readings of Hegel then provide resources to reconcile human freedom and constraint in religion.